Ring cavity multiwavelength brillouin-erbium fiber laser with a partially reflective fiber bragg grating - Johari M.I.; Adamiat A.; Shahabuddin N.S.; Nasir M.N.M.; Yusoff Z.; Abdul Rashid H.A.; Al-Mansoori M.H.; Choudhury P.K. (Optical Society of America (OSA), 2023)
Utilization of a partially reflective fiber Bragg grating in the development of a multiwavelength Brillouin- erbium fiber laser is proposed. A ring cavity with a preamplified Brillouin pump configuration is implemented to demonstrate much better performance in comparison with the previously reported results obtained with different configurations. The combination of a 7 km long single-mode fiber and a 10 m long erbium-doped fiber ultimately yields the generation of up to twenty-one Brillouin Stokes lines. The laser configuration provides a greater tuning range of 21 nm at a Brillouin pump power of 2 mW and 980 nm pump power of 20 mW, and requires a much lower pump power to initiate lasing. 2009 Optical Society of America.